Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/nph.15995
|View full text |Cite
|
Sign up to set email alerts
|

Are methane emissions from mangrove stems a cryptic carbon loss pathway? Insights from a catastrophic forest mortality

Abstract: Summary Growing evidence indicates that tree‐stem methane (CH4) emissions may be an important and unaccounted‐for component of local, regional and global carbon (C) budgets. Studies to date have focused on upland and freshwater swamp‐forests; however, no data on tree‐stem fluxes from estuarine species currently exist. Here we provide the first‐ever mangrove tree‐stem CH4 flux measurements from  >50 trees (n = 230 measurements), in both standing dead and living forest, from a region suffering a recent large‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 48 publications
3
44
0
Order By: Relevance
“…However, due to the variability in efflux from individual chamber measurements, no statistical difference was observed between efflux from living and dead forest areas (ANOVA, p = 0.16). This builds on recent work at the same study site revealing no difference in sediment CH 4 effluxes 32 months postforest dieback and an eightfold greater CH 4 efflux from dead mangrove tree stems, compared to living mangrove tree stems (Jeffrey et al 2019).…”
Section: Ch 4 Effluxsupporting
confidence: 70%
“…However, due to the variability in efflux from individual chamber measurements, no statistical difference was observed between efflux from living and dead forest areas (ANOVA, p = 0.16). This builds on recent work at the same study site revealing no difference in sediment CH 4 effluxes 32 months postforest dieback and an eightfold greater CH 4 efflux from dead mangrove tree stems, compared to living mangrove tree stems (Jeffrey et al 2019).…”
Section: Ch 4 Effluxsupporting
confidence: 70%
“…Firstly, our understanding of the biogeochemical processes of CH 4 production, consumption and transport in mangrove ecosystems is still nascent. While all these processes should be taken into account for a reliable estimate of net CH 4 efflux, the relative contributions of mangrove stems (Jeffrey et al, 2019), canopies (Keppler, Hamilton, Brass, & Röckmann, 2006), and coarse woody debris (Warner, Villarreal, McWilliams, Inamdar, & Vargas, 2017) as CH 4 sources are still highly uncertain. Secondly, Rosentreter et al (2018) assumed that mangroves were inundated by water for 50% of the time, which might not be representative of the tidal regimes in all mangrove environments.…”
Section: Reduced Emissions From Deforestation and Degradation And Globalmentioning
confidence: 99%
“…Tree-mediated emissions have recently been identified as an important component of CH 4 balance in wetlands, floodplains, and upland forests (Covey & Megonigal, 2019). Jeffrey et al (2019) showed that mangrove stem emission was a novel pathway of CH 4 release, with dead trees being more significant emitters of CH 4 than living trees that accounted for ~26% of the net ecosystem F CH4 . These findings suggested that the passive diffusion of CH 4 from soil to stem might be more important than the active transpiration of CH 4 in sustaining stem emissions, which would account for the weak link between LE and F CH4 observed in this study.…”
Section: Biophysical Drivers Of F Ch4mentioning
confidence: 99%
“…Tree density (tree m −2 ) is taken from Jeffrey et al () (their table 1). The value reported here is an average of three intertidal zones (upper, middle, and lower).…”
Section: Resultsmentioning
confidence: 99%